A method for preparing a lignocellulose full-component plastic based on a hemicellulose-priority full-dissolution system
Patent Information
- Application Number
- CN202610758972.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-20
AI Technical Summary
这种策略忽视了半纤维素在纤维素与木质素之间所起的“结构枢纽”关键作用,导致木质纤维素的整体解构不彻底,全组分协同转化效率低下
(1)溶解策略创新,突破传统局限
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomass material preparation technology, specifically relating to a method for preparing lignocellulose full-component plastics based on a hemicellulose-preferred fully dissolved system. Background Technology
[0002] Lignocellulose is the most abundant and renewable agricultural and forestry biomass resource. It is a core raw material for replacing fossil-based plastics and achieving green manufacturing and "dual carbon" goals for bio-based materials. It is mainly composed of cellulose, hemicellulose, and lignin, which are tightly interwoven through hydrogen bonds, ester bonds, ether bonds, and lignin-carbohydrate complexes (LCCs) to form a dense and rigid structure. The components are firmly bonded, difficult to dissolve, and difficult to separate, which has become a key bottleneck restricting the high-value utilization of all its components.
[0003] Existing dissolution strategies mostly adopt a "lignin-first" approach, focusing on the separation and extraction of single components. This strategy neglects the crucial "structural hub" role of hemicellulose between cellulose and lignin, resulting in incomplete overall deconstruction of lignocellulose and low efficiency in the synergistic conversion of all components. Furthermore, most systems cannot achieve a synergistic balance between stable hemicellulose retention, nanoscale cellulose dissociation, and mild lignin depolymerization under mild conditions. This makes it even more difficult to directly reconstitute the entire solution into a dense, well-balanced lignocellulose-based plastic in one step, severely limiting the industrialization of green biomass plastics.
[0004] Therefore, developing a novel fully dissolved system that prioritizes hemicellulose, is mild and efficient, allows for simultaneous dissolution of all components, enables solvent recyclability, and simplifies the recombination process, and achieves the integrated preparation of lignocellulose from "raw material → fully dissolved solution → fully-component plastic" has become a pressing technical challenge in this field. Summary of the Invention
[0005] The purpose of this section is to outline some aspects of the embodiments of the present invention and to briefly describe some preferred embodiments.
[0006] In view of the problems existing in the above and / or prior art, the present invention is proposed.
[0007] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing lignocellulose-based all-component plastics based on a hemicellulose-preferred fully dissolved system.
[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing lignocellulose-based fully dissolved plastics based on a hemicellulose-preferred fully dissolved system, comprising, ZnCl2, CaCl2 and H2O are mixed and dissolved under heating and stirring conditions to obtain a mixed solution; Add wood flour to the mixed solution, heat and stir to dissolve and form a homogeneous solution; Add water to the homogeneous solution and continue stirring. Let the resulting viscous solution stand to form a lignocellulose ion gel. The lignocellulose ionogel is immersed in ethanol to form an alcohol gel, which is then dried under pressure to obtain a lignocellulose complete component plastic.
[0009] In a preferred embodiment of the method described in this invention, ZnCl2, CaCl2 and H2O are mixed, wherein the mass ratio of ZnCl2, CaCl2 and H2O is 9.87 : 0.3 : 3.63.
[0010] In a preferred embodiment of the method described in this invention, the dissolution is carried out under heating and stirring conditions, wherein the heating temperature is 60~100℃. o C. The stirring speed is 400~600 rpm.
[0011] In a preferred embodiment of the method described in this invention, the wood flour is added to the mixed solution, wherein the mass ratio of wood flour to the mixed solution is 0.3~0.6:13.8.
[0012] In a preferred embodiment of the method described in this invention, the heating and stirring process to dissolve and form a homogeneous solution involves a heating temperature of 60-100°C. o C. Stirring speed is 400~600 rpm, and time is 20~60 min.
[0013] In a preferred embodiment of the method described in this invention, water is added to the homogeneous solution and stirring is continued, wherein the mass ratio of water to homogeneous solution is 2.5: 14.3~14.6.
[0014] In a preferred embodiment of the method described in this invention, the soaking time is 10-14 h.
[0015] In a preferred embodiment of the method described in this invention, the alcohol gel is dried under pressure, wherein the clamping force is controlled to be 0.1 MPa.
[0016] As a preferred embodiment of the method described in this invention, the drying is performed by natural ventilation, the relative humidity of the drying environment is 40-60%, and the drying time is 24 hours.
[0017] Another objective of this invention is to overcome the shortcomings of the prior art and provide a lignocellulose complete component plastic.
[0018] Another object of the present invention is to overcome the shortcomings of the prior art and provide an application of a lignocellulose full-component plastic as a substitute for petroleum-based plastics.
[0019] Beneficial effects of this invention: (1) Innovation in dissolution strategy, breaking through traditional limitations The hemicellulose-first total dissolution strategy replaces the mainstream "lignin-first" mode, rapidly disintegrating the LCC complex and achieving simultaneous total dissolution of all three components. This approach results in more thorough dissolution under milder conditions (low temperature and short time), solving the problems of insufficient dissolution and easy degradation of components in existing systems.
[0020] (2) All components are used efficiently with no waste. No need to separate and purify individual components; 100% of cellulose, hemicellulose, and lignin are retained and utilized, giving full play to the synergistic enhancement effect of the three components and significantly improving raw material utilization and overall material performance.
[0021] (3) The prepared lignocellulose whole-component plastic has excellent and balanced comprehensive properties. The prepared lignocellulose all-component plastic has high tensile strength, high toughness, good hydrophobicity, biodegradability, good interfacial compatibility, no obvious phase separation, and superior mechanical and water resistance properties compared to traditional single-component bio-based plastics. It is expected to serve as a substitute for disposable petrochemical plastics.
[0022] (4) The solvent is green and recyclable, making it environmentally friendly. ZnCl2 / H2O is a low-toxicity, easily synthesized, and low-cost green solvent with a recovery rate of ≥90% and stable recycling performance. It produces no strong acid or strong alkali waste liquid, meeting the requirements of green chemical industry and low-carbon manufacturing. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 The images shown are SEM images of lignocellulose before and after dissolution in an embodiment of the present invention.
[0024] Figure 2 This is a diagram showing the content of the three components in the cellulose residue of an embodiment of the present invention.
[0025] Figure 3 The images show lignocellulose ionogel and alcohol gel diagrams from embodiments of the present invention.
[0026] Figure 4The diagram shows a lignocellulose plastic and a water cup according to an embodiment of the present invention. Detailed Implementation
[0027] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0028] Example 1 Add 9.87 g of ZnCl2 to 3.63 g of deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.4 g of wood flour and add it to the ionic solution at 70 °C. o A homogeneous solution was obtained by maintaining a rotation speed of 600 rpm for 60 min at C.
[0029] Add 100 ml of acetone:water (v:v=1:1) mixture to the above solution and mix thoroughly. Then, perform solid-liquid separation by suction filtration. The collected solid residue was analyzed according to the method standard NREL / TP-510-42618. According to the test results, the contents of lignin, cellulose and hemicellulose were 24.4%, 39.9% and 7.66%, respectively. This result indicates that hemicellulose was preferentially dissolved. Note: The contents of cellulose, lignin and hemicellulose in the wood flour raw materials in all embodiments of the present invention are 41.6, 24.8 and 16.6 wt%, respectively.
[0030] Example 2 Add 9.87 g of ZnCl2 to 3.63 g of deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.4 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining a rotation speed of 600 rpm for 60 min at C.
[0031] Add 100 ml of acetone:water (v:v=1:1) mixture to the above solution and mix thoroughly. Then, perform solid-liquid separation by suction filtration. The collected solid residue was analyzed according to the method standard NREL / TP-510-42618. According to the test results, the contents of lignin, cellulose, and hemicellulose were 8.8%, 33.7%, and 2.7%, respectively. This result indicates that hemicellulose and cellulose were dissolved, and lignin was dissolved.
[0032] Example 3 Add 9.87 g of ZnCl2 to 3.63 g of deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.4 g of wood flour and add it to the ionic solution. (The solution is then prepared at 100°C.) o A homogeneous solution was obtained by maintaining a rotation speed of 600 rpm for 60 min at C.
[0033] 100 ml of acetone:water (v:v=1:1) mixture was added to the above solution and mixed thoroughly. The mixture was then filtered to separate the solid and liquid components. The collected solid residue was analyzed according to the method standard NREL / TP-510-42618. The results showed that the contents of lignin, cellulose, and hemicellulose were 6.5%, 28.7%, and 2.0%, respectively. This indicates that lignin was dissolved, but hemicellulose and cellulose showed varying degrees of degradation.
[0034] Example 4 Add 9.87 g of ZnCl2 to 3.63 g of deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.4 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining a rotation speed of 600 rpm for 20 min at C.
[0035] 100 ml of acetone:water (v:v=1:1) mixture was added to the above solution and mixed thoroughly. The mixture was then filtered to separate the solid and liquid components. The collected solid residue was analyzed according to the method standard NREL / TP-510-42618. The results showed that the contents of lignin, cellulose, and hemicellulose were 9.8%, 33.8%, and 3.7%, respectively. This indicates that hemicellulose and cellulose were dissolved, and lignin was also dissolved.
[0036] Example 5 Add 9.87 g of ZnCl2 to 3.63 g of deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.4 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 30 min at C.
[0037] Add 100 ml of acetone:water (v:v=1:1) mixture to the above solution and mix thoroughly. Then, perform solid-liquid separation by vacuum filtration. The collected solid residue was analyzed according to the method standard NREL / TP-510-42618. According to the test results, the contents of lignin, cellulose, and hemicellulose were 9.1%, 33.7%, and 3.5%, respectively. This result indicates that hemicellulose and cellulose were dissolved, and lignin was dissolved.
[0038] Example 6 Add 9.87 g of ZnCl2 to 3.63 g of deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.4 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 40 min at C.
[0039] Add 100 ml of acetone:water (v:v=1:1) mixture to the above solution and mix thoroughly. Then, perform solid-liquid separation by vacuum filtration. The collected solid residue was analyzed according to the method standard NREL / TP-510-42618. According to the test results, the contents of lignin, cellulose, and hemicellulose were 8.9%, 33.6%, and 2.8%, respectively. This result indicates that hemicellulose and cellulose were dissolved, and lignin was dissolved.
[0040] Example 7 Add 9.87 g ZnCl2 and 0.3 g CaCl2 to 3.63 g deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.3 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 40 min at C.
[0041] Slowly add 2.5 g of deionized water while simultaneously raising the temperature to 60°C. o C. Continue stirring for 10 min, then transfer to a mold and allow to stand at room temperature to form a lignocellulose ionogel. Immerse the ionogel in an ethanol solution for 12 h to remove inorganic salts and form an alcohol gel.
[0042] The alcohol gel was placed between two glass plates with a clamping force of 0.1 MPa and dried in air for 12 h until the ethanol was completely evaporated, resulting in a lignocellulose plastic (3*5cm) with a tensile stress of 32.6 MPa.
[0043] Example 8 Add 9.87 g ZnCl2 and 0.3 g CaCl2 to 3.63 g deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.4 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 40 min at C.
[0044] Slowly add 2.5 g of deionized water while simultaneously raising the temperature to 60°C. o C. Continue stirring for 10 min, then transfer to a mold and allow to stand at room temperature to form a lignocellulose ionogel. Immerse the ionogel in an ethanol solution for 12 h to remove inorganic salts and form an alcohol gel.
[0045] The alcohol gel was placed between two glass plates with a clamping force of 0.1 MPa and dried in air for 12 h until the ethanol was completely evaporated, resulting in a lignocellulose plastic with a tensile stress of 41.7 MPa.
[0046] Example 9 Add 9.87 g ZnCl2 and 0.3 g CaCl2 to 3.63 g deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.5 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 40 min at C.
[0047] Slowly add 2.5 g of deionized water while simultaneously raising the temperature to 60°C. o C. Continue stirring for 10 min, then transfer to a mold and allow to stand at room temperature to form a lignocellulose ionogel. Immerse the ionogel in an ethanol solution for 12 h to remove inorganic salts and form an alcohol gel.
[0048] The alcohol gel was placed between two glass plates with a clamping force of 0.1 MPa and dried in air for 12 h until the ethanol was completely evaporated, resulting in a lignocellulose plastic with a tensile stress of 50.3 MPa.
[0049] Example 10 Add 9.87 g ZnCl2 and 0.3 g CaCl2 to 3.63 g deionized water and heat to 60°C. o C. Stir to form a homogeneous ionic solution; Weigh 0.6 g of wood flour and add it to the ionic solution, then heat at 90°C. o At C, maintain a rotation speed of 600 rpm for 40 min to obtain a homogeneous solution. Slowly add 2.5 g of deionized water while simultaneously raising the temperature to 60°C. o C. Continue stirring for 10 minutes, then transfer to a mold and let stand at room temperature to form a lignocellulose ionogel.
[0050] The ionogel was immersed in an ethanol solution for 12 h to remove inorganic salts and form an alcohol gel.
[0051] The alcohol gel was placed between two glass plates with a clamping force of 0.1 MPa and dried in air for 12 h until the ethanol was completely evaporated, resulting in a lignocellulose plastic with a tensile stress of 48.4 MPa.
[0052] Analysis of the cellulose residue components after dissolution of lignocellulose in Examples 1, 2, and 3 shows that, in the several steps included in this invention, the higher the dissolution temperature, the lower the hemicellulose content, and cellulose and lignin dissolve sequentially. Preferably, 90°C is used. o C represents the pretreatment temperature at which lignocellulose is completely dissolved.
[0053] Based on the component analysis data of the cellulose residue after dissolving lignocellulose in Examples 2, 4, 5, and 6, it can be seen that the several steps included in this invention, while maintaining 90°C... o At temperature C, as the pretreatment time increases from 20 min to 60 min, the contents of hemicellulose, cellulose and lignin gradually decrease. When the pretreatment time is 40 min, the component contents remain basically unchanged. 40 min is the preferred pretreatment time for lignocellulose.
[0054] The mechanical property data of the lignocellulosic plastics prepared in Examples 7, 8, 9, and 10 show that increasing the wood flour content can enhance the tensile strength of the plastic. When the wood flour content is increased from 0.3 g to 0.5 g, the tensile strength increases from 32.6 MPa to 50.3 MPa. When the content increases to 0.6 g, the tensile strength decreases. 0.5 g of wood flour is preferred for preparing lignocellulosic plastics.
[0055] Depend on Figure 1 As can be seen, in the treatment of the present invention (Example 6), the wood flour is transformed from larger particles into a structure that is a mixture of nanofibers and lignin particles.
[0056] Depend on Figure 2 As can be seen from the analysis of the cellulose residue after the treatment of the present invention (Example 6), the relative contents of hemicellulose, cellulose and lignin are 2.8, 33.6 and 8.9%, respectively.
[0057] Depend on Figure 3 As can be seen, during the preparation process of this invention, the color of the lignocellulose ion gel and alcohol gel (Example 9) is brown.
[0058] Depend on Figure 4 As can be seen, the lignocellulose plastic prepared by the present invention is brown in color (Example 9) and has a thickness of about 50 μm.
[0059] Comparative Example 1 Add 9.87 g ZnCl2 and 0.3 g CaCl2 to 3.63 g deionized water, heat to 60°C and stir to form a homogeneous ionic solution; Weigh 0.5 g of wood flour and add it to the ionic solution at 80 °C. o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 40 min at C.
[0060] Slowly add 2.5 g of deionized water while simultaneously raising the temperature to 60°C. o C. Continue stirring for 10 minutes, then transfer to a mold and let stand at room temperature to form a lignocellulose ionogel.
[0061] The ionogel was immersed in an ethanol solution for 12 h to remove inorganic salts and form an alcohol gel.
[0062] The alcohol gel was placed between two glass plates with a clamping force of 0.1 MPa and dried in air for 12 h until the ethanol was completely evaporated, resulting in a lignocellulose plastic with a tensile stress of 46.5 MPa.
[0063] Comparative Example 2 Add 9.87 g ZnCl2 and 0.3 g CaCl2 to 3.63 g deionized water, heat to 60°C and stir to form a homogeneous ionic solution; Weigh 0.5 g of wood flour and add it to the ionic solution. (The solution is then prepared at 100°C.) o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 40 min at C.
[0064] Slowly add 2.5 g of deionized water while simultaneously raising the temperature to 60°C. o C. Continue stirring for 10 minutes, then transfer to a mold and let stand at room temperature to form a lignocellulose ionogel.
[0065] The ionogel was immersed in an ethanol solution for 12 h to remove inorganic salts and form an alcohol gel.
[0066] The alcohol gel was placed between two glass plates with a clamping force of 0.1 MPa and dried in air for 12 h until the ethanol was completely evaporated, resulting in a lignocellulose plastic with a tensile stress of 5.5 MPa.
[0067] Comparative Example 3 The optimal concentration of ZnCl2 in the system was approximately 72 wt%. The results were as follows when the concentration was adjusted to 65 wt%: Weigh 0.5 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 40 min at C.
[0068] Slowly add 2.5 g of deionized water while simultaneously raising the temperature to 60°C. o C. Continue stirring for 10 minutes, then transfer to a mold and let stand at room temperature to form a lignocellulose ionogel.
[0069] The ionogel was immersed in an ethanol solution for 12 h to remove inorganic salts and form an alcohol gel.
[0070] The alcohol gel was placed between two glass plates with a clamping force of 0.1 MPa and dried in air for 12 h until the ethanol was completely evaporated, resulting in a lignocellulose plastic with a tensile stress of 16.8 MPa.
[0071] Comparative Example 4 The optimal concentration of ZnCl2 in the system was approximately 72 wt%. The results were as follows when the concentration was adjusted to 80 wt%: Weigh 0.5 g of wood flour and add it to the ionic solution, then heat at 90°C. o A homogeneous solution was obtained by maintaining the rotation speed at 600 rpm for 40 min at C.
[0072] Slowly add 2.5 g of deionized water while simultaneously raising the temperature to 60°C. o C. Continue stirring for 10 minutes, then transfer to a mold and let stand at room temperature to form a lignocellulose ionogel.
[0073] The ionogel was immersed in an ethanol solution for 12 h to remove inorganic salts and form an alcohol gel.
[0074] The alcohol gel was placed between two glass plates with a clamping force of 0.1 MPa and dried in air for 12 h until the ethanol was completely evaporated, resulting in a lignocellulose plastic with a tensile stress of 31.6 MPa.
[0075] For the pretreatment of lignocellulose, most methods employ a lignin-first strategy. This invention proposes a hemicellulose-first strategy. Current lignocellulose composite membranes involve pretreatment followed by mixing of components for membrane formation. This invention directly dissolves the three components in wood flour and reassembles them in situ for membrane formation, resulting in a simple and efficient process. This invention uses a hemicellulose-first, fully dissolved strategy, replacing the mainstream "lignin-first" approach. This rapidly disintegrates the LCC composite, achieving simultaneous and complete dissolution of all three components. The dissolution is more thorough and the conditions are milder (low temperature, short time), solving the problems of insufficient dissolution and easy degradation of components in existing systems.
[0076] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.
Claims
1. A method for preparing lignocellulose-based all-component plastics using a hemicellulose-preferred fully dissolved system, characterized in that: include, ZnCl2, CaCl2 and H2O are mixed and dissolved under heating and stirring conditions to obtain a mixed solution; Add wood flour to the mixed solution, heat and stir to dissolve and form a homogeneous solution; Add water to the homogeneous solution and continue stirring. Let the resulting viscous solution stand to form a lignocellulose ion gel. The lignocellulose ionogel is immersed in ethanol to form an alcohol gel, which is then dried under pressure to obtain a lignocellulose complete component plastic.
2. The method as described in claim 1, characterized in that: The mixture of ZnCl2, CaCl2 and H2O is wherein the mass ratio of ZnCl2, CaCl2 and H2O is 9.87 : 0.3 : 3.
63.
3. The method as described in claim 1, characterized in that: The dissolution is carried out under heating and stirring conditions, wherein the heating temperature is 60~100℃. o C. The stirring speed is 400~600 rpm.
4. The method as described in claim 1 or 2, characterized in that: The wood flour is added to the mixed solution, wherein the mass ratio of wood flour to the mixed solution is (0.3~0.6):13.
8.
5. The method as described in claim 1 or 2, characterized in that: The heating and stirring process dissolves the material to form a homogeneous solution, wherein the heating temperature is 60~100°C. o C. Stirring speed is 400~600 rpm, and time is 20~60 min.
6. The method as described in claim 1 or 2, characterized in that: Water is added to the homogeneous solution and stirring continues, with the mass ratio of water to homogeneous solution being 2.5: (14.3~14.6).
7. The method as described in claim 1 or 2, characterized in that: The soaking time is 10-14 hours.
8. The method as described in claim 7, characterized in that: The alcohol gel is dried under pressure, wherein the clamping force is controlled to be 0.1 MPa.
9. The method as described in claim 1, characterized in that: The drying process is a natural ventilation drying process, with a relative humidity of 40-60% in the drying environment and a drying time of 24 hours.
10. The use of the lignocellulose whole-component plastic prepared by any one of claims 1 to 9 as a substitute for petroleum-based plastics.